Transversal city and transtopia - reflecting and analyzing migration, the city, and "the urban" after the postmigrant city. - West, Christina (Geographisch-Ethnographische Gesellschaft Zürich, 2019)
"Transversal city" and transtopia are an invitation to rethink, conceptually and empirically, our urban future. Individual actors, persons with and without migration/flight background, today appear more and more transversal with respect to how they perceive the world, how they give themselves an identity, how they confront others, and how they observe, reflect, and produce knowledge. Previous "modern" static, clearly defined, and discernible constructions of belonging, which follow the "either/or" logic of socio-structural statistical ordering schemes, are actively rejected in a reflected way. Instead, belonging and identity are constructed individually following a reasoning which is transversal: spontaneously, situationally, by improvisation, oriented to potentials, crossing boundaries, transgressing, and generating abstract order and multiple references. Observed transgressive tendencies are discussed starting from a postmigrant perspective, which is part of the recent migration discourse. By identification of four main characteristic discursive moments, transversality is conceptualized, analyzed, and differentiated from the explicitly postmigrant perspective, which is part of the critical perspective. Instead, the concept of the "transversal city" arises with its changed modes of knowledge production, its consequences for social justice and sustainable development, and the evolution of a new processuality of governance, in politics and planning, urban agendas, and the production of "the urban".
Keywords: Stadtsoziologie; Stadtforschung; Stadtentwicklung; Stadtplanung; Migration; Integration; Interkulturalität; Postmoderne